TINJAUAN PENYEBAB KLAIM PENDING BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI RSU HAJI SURABAYA - Ariqpurna Bayu Triatmaja; Rossalina Adi Wijayanti; Novita Nuraini (Politeknik Negeri Jember, 2022)
Badan Pelaksana Jaminan Sosial (BPJS) Kesehehatan provide health services to the public by using a prospective payment system. Surabaya Hajj General Hospital is one of the type B educational hospitals that has been collaborating with the BPJS since 2014. Based on primary data at Surabaya Haji Hospital it was found that the claim file had pending claims. This is due to incomplete claim file, inaccurate diagnostic code due to differences in perception between the coders and verifiers. This study aims to analyze the pending claims factor of the Health Social Security Administration Agency (BPJS) at Haji Hospital Surabaya. Problem identification uses 5M management elements (man, material, methods, machine, money). This type of research is descriptive qualitative, narrating the results of the study. In the man element that causes the pending claim is the officer still feels difficulty in reading the diagnoses and actions of patients due to the writing of doctors who are difficult to read, and incorrect diagnosis codes and actions due to differences in perception between the coder and verifier of the BPJS. The material element that causes the pending claim is the incomplete claim file, such as the results of patient support examinations. In the Method element that causes pending claims, there is no SOP governing the filling of a specific diagnosis file claim. On the machine element that causes pending claims is the computer used in the claim submission process often experiences long loading times and often experiences network disruptions. In the element of money in this study does not cause pending claims, because casemix officers can not know the amount of loss caused by pending claims.